2008
DOI: 10.1002/rmv.590
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C and renal transplantation: a review on historical aspects and current issues

Abstract: Chronic liver disease has a significant impact on the survival of renal transplant recipients with an incidence rate of 4-38%. Approximately, 8-28% of renal transplant recipients die due to chronic liver disease. Hepatitis C seems to be the leading cause of chronic liver disease in kidney recipients. Hepatitis C virus (HCV) infection has a wide range of prevalence (2.6-66%) among renal transplant recipients living in different countries with great genotype diversity in different parts of the world. Nowadays, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 143 publications
0
8
0
Order By: Relevance
“…In a previous survey in Iran, HCV RNA was detected in 6.4% of liver transplant recipients (26). Moreover, the infection in renal transplant recipients varies between 2.6% and 66% in different geographical areas of the world (27)(28)(29).…”
Section: Discussionmentioning
confidence: 95%
“…In a previous survey in Iran, HCV RNA was detected in 6.4% of liver transplant recipients (26). Moreover, the infection in renal transplant recipients varies between 2.6% and 66% in different geographical areas of the world (27)(28)(29).…”
Section: Discussionmentioning
confidence: 95%
“…In a meta-analysis, Fabrizi et al identified 24 clinical trials with 529 unique patients, where a summary estimate of SVR was 39% (95% CI 32-46) and a drop-out rate of 19% (95% CI [13][14][15][16][17][18][19][20][21][22][23][24][25][26] [80••]. The main reasons for discontinuation of therapy were flu like symptoms, gastro-intestinal and hematological adverse effects.…”
Section: Interferon Monotherapymentioning
confidence: 99%
“…The prevalence of anti-HCV antibodies among kidney recipients ranges from 2.6% to 66% dependant on country of origin and transplant center [13]. Most renal transplant recipients have acquired HCV infection prior to transplantation [14].…”
Section: Renal Transplant Patientsmentioning
confidence: 99%
“…1,2 The diversity of these rates results from differences between centers, countries, and geographic areas. 3 The prevalence of HCV infection is higher in renal transplant recipients (11% to 49%) than the hemodialysis population. 4,5 There is controversy regarding the long-term outcomes following kidney transplant between patients who have or do not have HCV.…”
Section: Introductionmentioning
confidence: 99%